Content location for in-flight entertainment systems based on peer-to-peer networks - Renzo Zamprogno Loureiro (2009)
In this work we introduce a peer-to-peer approach for in-flight entertainment video on-demand systems. Such applications are traditional ways for the airline to improve profit from its operation and attract customers. We outline how a peer-to-peer system should be organized to address this specific application and reduce operational costs for the airline. Furthermore, we discuss in details the problem of content discovery that rises in such environment and propose two feasible solutions. These solutions are analyzed in the terms of network bandwidth demand and amount of data transmitted over the network infrastructure. Our conclusions show that the content location problem can be solved without significant use of bandwidth, and ultimately the peer-to-peer paradigm is a worth-taking and feasible path for the next in-flight entertainment system generations.